Bibliometric Analysis of Quality Assurance In Indonesian Islamic Higher Education: Mapping the Knowledge Landscape and Policy Implications - Abd Warits; Mohammad Faizul Husnayain; Imaduddin Imaduddin; Paisun Paisun; Abdul Azis (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2026)
Indonesian Islamic higher education institutions face a distinctive dual mandate of maintaining religious authenticity whilst achieving global academic competitiveness. However, the causal mechanisms linking innovation to competitive advantage in this context remain systematically underexplored. This study presents a bibliometric analysis of quality assurance and innovation research in Indonesian Islamic higher education from 2015 to 2025, aiming to map the intellectual landscape, identify thematic evolution, and examine collaboration patterns within this emerging field. Using Publish or Perish (Version 8) for data extraction and VOSviewer (Version 1.6.20) for network analysis, 500 publications were retrieved from Google Scholar and systematically screened in accordance with PRISMA 2020 guidelines. Citation analysis was conducted on a subset of 198 publications with complete metadata, yielding 2,208 total citations and an h-index of 22. Five thematic clusters were identified: Innovation-Competitiveness Nexus (35–40% of keywords), Quality Assurance Systems (25–28%), Islamic Higher Education Context (18–22%), Leadership and Governance (12–15%), and Stakeholder Engagement (8–10%). Temporal analysis reveals a three-phase evolution from descriptive quality assurance documentation (2015–2018) toward deeper theoretical development of the relationship between innovation and competitive advantage (2022–2025). Analysis of the same subset further demonstrates limited and dispersed collaboration patterns among authors, with a mean authorship of 2.18, a network density of 0.14, and an international co-authorship rate of 8.1%. These findings yield a triple-pathway theoretical proposition quality assurance infrastructure, digital transformation capacity, and Islamic identity integration through which innovation may translate into competitive advantage, extending Dynamic Capabilities frameworks to religious institutional contexts